Observations on the efficacy of edaravone dexborneol in preventing post-stroke depression and its inflammatory mechanism: a prospective, randomized, control trial - Xu, Mingyuan; Li, Lan; Xu, Bu; Yuan, Shanfang; Zheng, Qin; Sun, Wenjun (Frontiers in Neuroscience, 2024)
ObjectiveThis study aimed to observe the effect of edaravone dexborneol (EDB) on the incidence of early post-stroke depression (PSD) and explore its inflammatory mechanisms.MethodsA prospective, randomized controlled study was conducted from January 2022 to June 2023, involving patients with acute ischemic stroke (AIS) at the Neurology Department of the Third Affiliated Hospital of Beijing University of Traditional Chinese Medicine. The control group received routine treatment, while the experimental group received routine combined EDB treatment. The main outcome measures included PSD incidence, Patient Health Questionnaire (PHQ-9) and Hamilton Depression Scale (HAMD) scores on days 14 and 30, and inflammatory factor levels on day 14.ResultsA total of 93 patients were included in the study, 51 in the experimental group and 42 in the control group. On day 14, the PSD incidence was 13.7% in the experimental group, lower than 31.0% in the control group (95%CI 0.127–0.996; p = 0.044). Compared to the control group, the experimental group showed significantly lower concentrations of pro-inflammatory cytokines IL-1β (95%CI 3.353–5.184), IL-6 (95%CI 2.694–3.426), TNF-α (95%CI 4.985–12.196), IFN-γ (95%CI 0.163–0.451), MCP-1 (95%CI 0.335–0.787), IL-17A (95%CI 0.543–1.024), and IL-23p19 (95%CI 1.677–1.959) (all p < 0.001), and higher levels of anti-inflammatory cytokines IL-4 (95%CI −1.087 to −0.941), IL-10 (95%CI −6.125 to −1.662), and IL-13 (95%CI −6.078 to −2.953) (all p ≤ 0.001). On day 30, the PSD incidence in the experimental group was 15.7%, lower than 40.5% in the control group (95%CI 0.103–0.725; p = 0.007). Compared with the control group, the experimental group had lower PHQ-9 scores on day 14 (95%CI 0.034–1.577; p = 0.041) and day 30 (95%CI 0.018–1.573; p = 0.045), and also had lower HAMD scores on day 14 (95% CI 0.281–2.856; p = 0.018) and day 30 (95% CI 0.647–3.482; p = 0.005).ConclusionEDB could reduce the incidence of early PSD, reduce pro-inflammatory cytokine levels, and elevate anti-inflammatory cytokine levels, which was possibly related to the anti-inflammatory mechanism of EDB.Clinical trial registrationhttp://www.chictr.org.cn/, identifier [ChiCTR2300067750].